2020
DOI: 10.1002/chem.202002513
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Diarsene Complex [(C5H5)2Mo2(CO)4(μ,η2‐As2)] as a Connector Between Silver Ions

Abstract: The reactiono ft he organometallic diarsene complex [Cp 2 Mo 2 (CO) 4 (m,h 2-As 2)] (B)(Cp = C 5 H 5)w ith Ag[FAl{OC 6 F 10 (C 6 F 5)} 3 ](Ag[FAl]) and Ag[Al{OC(CF 3) 3 } 4 ] (Ag[TEF]), respectively,y ields three unprecedenteds upramolecular assemblies [(h 2-B) 4 Ag 2 ][FAl] 2 (4), [(m,h 1 :h 2-B) 3 (h 2-B) 2 Ag 3 ][TEF] 3 (5)a nd [(m,h 1 :h 2-B) 4 Ag 3 ][TEF] 3 (6). These products are only composed of the complexes B andA g I. Moreover,c ompounds 5 and 6 are the only supramolecular assemblies featuring B as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
(25 reference statements)
0
6
0
3
Order By: Relevance
“…51 The As−Tl interactions are between 3.168(1) Å and 3.545(1) Å, which is fairly long, but still significantly below the sum of their van der Waals radii (3.81 Å). 50 A comparable coordination mode of the Tl(I) atoms in [D] 5 Tl 2 has not been observed in any other coordination compound of D. 34,35 Although However, both show a tetrahedral coordination environment and their distance (Tl1−Tl2:3.882(2) Å) is slightly below the sum of the van der Waals radii (3.92 Å). 50 Thus, a Tl•••Tl interaction appears plausible.…”
Section: ■ Introductionmentioning
confidence: 79%
“…51 The As−Tl interactions are between 3.168(1) Å and 3.545(1) Å, which is fairly long, but still significantly below the sum of their van der Waals radii (3.81 Å). 50 A comparable coordination mode of the Tl(I) atoms in [D] 5 Tl 2 has not been observed in any other coordination compound of D. 34,35 Although However, both show a tetrahedral coordination environment and their distance (Tl1−Tl2:3.882(2) Å) is slightly below the sum of the van der Waals radii (3.92 Å). 50 Thus, a Tl•••Tl interaction appears plausible.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Zur Klärung der Koordinationsformen von C gegenüber Metallionen und zum Vergleich mit denen der leichteren Phosphor‐( A ) und Arsen‐( B ) Analoga, [9c] wurden Natural Bonding Orbital(NBO)‐Rechnungen für die Verbindungen A – C auf dem B3LYP [28] /def2‐TZVP [29] ‐Niveau der Theorie durchgeführt. Diese Rechnungen zeigen, dass das Energieniveau der Sb‐Sb‐σ‐Bindung in C höher ist als das der As‐As‐σ‐Bindung in B , welches wiederum höher ist als das der P‐P‐σ‐Bindung in A , woraus sich ein klarer Trend ergibt (Abbildung 1).…”
Section: Ergebnisse Und Diskussionunclassified
“…Um diese Lücke zu schließen, entwickelte unsere Gruppe das Konzept der Verwendung metallorganischer Polyphosphor (P n ) ( n =2–6)‐ und Polyarsen (As n ) ( n =2–3, 5)‐Ligandkomplexe als Liganden für Ag I ‐ und andere Metallionen [9] . Dieses Konzept ermöglichte die Synthese einer neuartigen Klasse von Supramolekülaggregaten, die diskrete supramolekulare Koordinationskomplexe (SCCs) (Monomere, [9a,b] Dimere, [9b,c,e, 10] Oligomere, [9c] anorganische Fulleren‐artigen Nanosphären, [11] nano‐dimensionierte Hemisphären [12] und Kapseln [13] ) sowie 1D‐, 2D‐ und selbst 3D‐Koordinationspolymere (CPs) einschließt [10a, 14] . Zu den einfachsten P n ‐ und As n ‐Verbindungen gehören die Diphosphor‐ und Diarsen‐Ligandkomplexe [Cp 2 Mo 2 (CO) 4 (η 2 ‐E 2 )] (E=P ( A ), [15] As ( B ), [16] Cp=C 5 H 5 ).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The results showed that either the lone pairs located on the P or E atoms of the tetrahedral complexes or the P−E/E−E σ‐orbital are donated to the coinage metal centers. Indeed, detailed theoretical calculations on A – E show that the lone pairs located on As and Sb atoms are lower in energy than that of the P atoms [12b–c,e] . Further, the inclusion of a heavier group 15 hetero‐atom as in B and C elevated the energy of the P−E σ‐bond.…”
Section: Introductionmentioning
confidence: 99%